Clinicoradiological, pathological, and surgical outcome in patients with tethered cord syndrome: A prospective study - Sridham Sutradhar; Anand Sharma; Avinash Sharma; Harsh Deo Pandey; Kiran Ahire (Asian Journal of Medical Sciences, 2024)
Background: Tethered cord syndrome (TCS) is a stretch-induced functional disorder of the spinal cord in which the caudal part is anchored by an inelastic structure. It is believed that, if the viscoelasticity of the filum is lost or compromised by either fatty infiltration or abnormal thickening, caudal tension and traction may cause undue stress upon the conus, resulting in TCS. It typically occurs in children, and it is rare in adults. Aims and Objectives: The study was conducted to know the clinicoradiological, pathological, and surgical outcomes in patients with TCS. Materials and Methods: This is a prospective observational study done in the premier institute of central India from May 2022 to April 2024. This study included patients who exhibited clinical and/or radiological features of congenital tethered cords. This encompassed both patients with tethered cord and those with TCS. Patients who failed to give consent and refused to participate in the study were excluded from the study. Results: A total of 30 patients were recruited for the study. The median age of the patients was 6–12 months (range). The gender distribution M:F was 63.3:36.6. Based on 30 cases studied, most of the patients (75%) had improvement in urinary symptoms, 57.1% of patients had improvement in bowel symptoms, 80% of patients had improvement in pain symptoms, 75% had improvement in motor deficit, and 83.3% had improvement in sensory deficit. Conclusion: Our prospective, cross-sectional study aimed at complete detethering of the spinal cord and the nerve roots along with excision of filum terminale and dural reconstruction to maintain adequate cerebrospinal fluid space around the spinal cord to prevent retethering.